2006
DOI: 10.1111/j.1365-2257.2006.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care testing of neonatal coagulation

Abstract: The aim of this validation study was to compare prothrombin time (PT) and activated partial thromboplastin time (APTT) results from a point-of-care testing (POCT) device (Rapidpoint Coag) with those from standard laboratory tests. The subjects were newborn infants needing coagulation screen for any clinical indications within a regional neonatal intensive care unit. The level of agreement between POCT and laboratory measurements of PT and APTT was determined. For PT: the bias was from -7.6 to 12.4 s and precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Its advantages include the need for small volumes of blood, reducing the risk of iatrogenic anaemia,2 and the timely availability of results, diminishing the interval between receipt of a result and therapeutic intervention 2…”
mentioning
confidence: 99%
“…Its advantages include the need for small volumes of blood, reducing the risk of iatrogenic anaemia,2 and the timely availability of results, diminishing the interval between receipt of a result and therapeutic intervention 2…”
mentioning
confidence: 99%
“…The American College of Chest Physicians, at the Eighth Consensus Conference on Antithrombotic and Thrombolytic Therapy, concluded that accuracy of point-of-care monitors for heparin therapy had thus far not been established [9]. A previously published study (with a different bedside device) in neonates reported underestimation at lower aPTT levels, and overestimation at higher levels [11]. The main finding of this study was that the bedside device substantially overestimated the aPTT in infants treated with heparin.…”
Section: Discussionmentioning
confidence: 55%
“…Screening for coagulopathy can be technically difficult, as samples heparin-contaminated samples and a relatively large volume of blood is required equivalent to 3% of circulatory volume in a 500 g infant. Further studies may become more practical in this era of point-of-care (POC) technology using smaller samples [23].…”
Section: Discussionmentioning
confidence: 99%